An Analysis of The Students’ Speaking Mastery Through The Speech Extracurricular Activity at MTs Nu Malintang Jae - Atikah, Luri; Hasibuan, Sri Wahyuni; Yahsya, Akhrif (MUDABBIR Journal Research and Education Studies, 2025)
Limited public speaking Mastery among students highlight the need for structured guidance and continuous practice. To address this issue, MTs. NU Malintang Jae implemented a speech extracurricular activity as a platform to enhance students’ speaking Mastery. This study aimed to analyze students' speaking skills and identify the challenges they faced during the activity. A qualitative field study method was used, involving 25 eighth-grade students. Data were collected through interviews, observations, and documentation. The analysis involved data reduction, data presentation, and conclusion drawing. The findings showed that 52% of students had a "very good" level of speaking Mastery, 28% were at a "good" level, and 20% were at a "fair" level. Challenges were observed in fluency, pronunciation, grammar, vocabulary, and audience engagement. Specific difficulties were related to psychological factors (8 students), linguistic factors (12 students), environmental factors (1 student), and public speaking skill factors (4 students). These were mainly associated with lack of confidence and speaking-related anxiety. It is recommended that speech extracurricular activities provide more targeted support and practice opportunities to help students overcome these challenges and improve their speaking performance.